Genetic analysis reveals functions of atypical polyubiquitin chains - Meza Gutierrez, Fernando; Simsek, Deniz; Mizrak, Arda; Deutschbauer, Adam; Braberg, Hannes; Johnson, Jeffrey; Xu, Jiewei; Shales, Michael; Nguyen, Michelle; Tamse-Kuehn, Raquel; Palm, Curt; Steinmetz, Lars M; et al. (eLife, 2018)
Although polyubiquitin chains linked through all lysines of ubiquitin exist, specific functions are well-established only for lysine-48 and lysine-63 linkages in Saccharomyces cerevisiae. To uncover pathways regulated by distinct linkages, genetic interactions between a gene deletion library and a panel of lysine-to-arginine ubiquitin mutants were systematically identified. The K11R mutant had strong genetic interactions with threonine biosynthetic genes. Consistently, we found that K11R mutants import threonine poorly. The K11R mutant also exhibited a strong genetic interaction with a subunit of the anaphase-promoting complex (APC), suggesting a role in cell cycle regulation. K11-linkages are important for vertebrate APC function, but this was not previously described in yeast. We show that the yeast APC also modifies substrates with K11-linkages in vitro, and that those chains contribute to normal APC-substrate turnover in vivo. This study reveals comprehensive genetic interactomes of polyubiquitin chains and characterizes the role of K11-chains in two biological pathways.
Keywords: ubiquitin; K11; APC